Hierarchically structured electrodes for moldable supercapacitors by synergistically hybridizing vertical graphene nanosheets and MnO2. (February 2021) - Zhou, Yang; Cheng, Xinying; Huang, Feng; Sha, Zhao; Han, Zhaojun; Chen, Junyan; Yang, Wenmu; Yu, Yuyan; Zhang, Jin; Peng, Shuhua; Wu, Shuying; Rider, Andrew; et al.
Abstract: Achieving moldable energy storage devices will make it possible to power wearable electronics by adapting to body contours for wear comfort. Herein, we present a new approach to create hierarchically structured electrodes that enable supercapacitors to retain their capacity under mechanical deformation. The electrodes are made by first growing vertical graphene nanosheets (VGNs) and then depositing manganese oxide (MnO2 ) on ductile nickel wires. Two such electrodes are made into a moldable supercapacitor using a solid-state electrolyte containing carboxymethylcellulose and sodium sulfate. This foldable supercapacitor achieves a high areal capacitance up to 56 mF cm −2, areal energy density of 7.7 μWh cm −2, and areal power density of 5 mWh cm −2 . These exceptional properties originate from the synergy between VGNs and MnO2, where the highly porous VGNs serve two critical functions: a mechanically robust platform of large surface area allowing high mass loading deposition of pseudocapacitive MnO2 and an interconnected conductive network for efficient electron/ion transport. Fiber-shaped supercapacitors made from these electrodes can be molded into different shapes by bending and twisting with little performance loss. The promising results presented in this study provide a new route for fabricating high-performance moldable energy storage devices for wearable electronics and wireless electronic skins. Graphical abstract: Image 1